Modeling, Simulation and Analysis of Induction Motor for Electric Vehicle Application - Yusof, Yushaizad; Mat, Kamarulzaman (International Journal of Engineering and Technology, 2018)
High power induction motor (IM) is widely used in industries and recently has been put into electric vehicle as the replacement of the internal combustion engine. In order to study the characteristics of the IM, a model of three-phase squirrel cage induction motor is designed and developed using MATLAB Simulink tool. Synchronous reference frame (SRF) technique is implemented to simplify the equivalent circuit model. Based on state space form, a flux linkage equation is developed using three stages transformation matrices. It demonstrated a good performance with fast response for AC start-up test, where simulated induced torque, rotor speed, mechanical output power, efficiency, slip and stator current waveforms were generated accordingly.Â  Indeed, the developed IM model can be used as a starting platform to further study and analyses the IM drives performance for electric vehicle application.Â